Fantasia di sparizione - Vari, Autori (Il sogno della farfalla, 2009)
The talks given by G. Bonetta, A. Homberg and M. Pettini are published here, as well as the debate that followed, on the occasion of the presentation of Massimo Fagioli’s eighth book Disappearance fantasy at the Università of Chieti-Pescara “G. d’Annunzio”, on 21st March 2009, containing the lessons held in 2007 at the same University. The themes dealt with on this occasion relate to the birth theory elaborated by Fagioli, and its polemical placing in respect to the history of drives, its scientific status, and its implications not only in the psychiatric field, but also in the pedagogic, political and philosophical fields, as well as the fundamental distinction that it proposes between disappearance fantasy and annulment drive.